2015
DOI: 10.3238/arztebl.2015.0423
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis and Treatment of Systemic Lupus Erythematosus

Abstract: The long-term prognosis for SLE has improved markedly in recent decades because of earlier diagnosis and optimized treatment. Further research and randomized controlled trials are needed for the development of specifically targeted therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
139
0
23

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(167 citation statements)
references
References 68 publications
(41 reference statements)
5
139
0
23
Order By: Relevance
“…17 One female systemic lupus erythematosus case with typical malar rash, ulcerative lesions over lips, labial mucosa and tongue was screened associated with joint pain, respiratory tract infection similar to earlier reports. 4,18 One 80 year old female patient presented with ulcerative lesion over lower lip associated with burning sensation and histological features were consistent with that of discoid lupus erythematous which is similar to other studies. 4,18 Total 22 cases of premalignant conditions were diagnosed with most common etiologies being leukoplakia followed by oral submucous fibrosis.…”
Section: Fig 5: a Psoriasis Case Presented With Fissured Tonguesupporting
confidence: 71%
See 1 more Smart Citation
“…17 One female systemic lupus erythematosus case with typical malar rash, ulcerative lesions over lips, labial mucosa and tongue was screened associated with joint pain, respiratory tract infection similar to earlier reports. 4,18 One 80 year old female patient presented with ulcerative lesion over lower lip associated with burning sensation and histological features were consistent with that of discoid lupus erythematous which is similar to other studies. 4,18 Total 22 cases of premalignant conditions were diagnosed with most common etiologies being leukoplakia followed by oral submucous fibrosis.…”
Section: Fig 5: a Psoriasis Case Presented With Fissured Tonguesupporting
confidence: 71%
“…4,18 One 80 year old female patient presented with ulcerative lesion over lower lip associated with burning sensation and histological features were consistent with that of discoid lupus erythematous which is similar to other studies. 4,18 Total 22 cases of premalignant conditions were diagnosed with most common etiologies being leukoplakia followed by oral submucous fibrosis. In the present study, premalignant conditions showed association with smoking and use of other forms of tobacco with a significant male preponderance.…”
Section: Fig 5: a Psoriasis Case Presented With Fissured Tonguesupporting
confidence: 71%
“…To date, 2 S1P (1) receptor modulators have been granted marketing authorization for the treatment of multiple sclerosis . Cenerimod is under clinical development for the treatment of systemic lupus erythematosus (SLE), a complex autoimmune disorder of chronic nature that involves autoreactive T and B lymphocytes causing inflammation and tissue damage . Preventing organ invasion and damage by reducing their tissue availability with S1P 1 receptor modulators is thus considered a promising therapeutic approach for the treatment of SLE.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were excluded if they presented: (1) at least one of the clinical criteria and one of the laboratory criteria for Antiphospholipid antibody syndrome [9] and/or (2) clinical and immunological criteria for Systemic Lupus Erythematous [10] or (3) any thrombophilic state.…”
Section: Patient Selectionmentioning
confidence: 99%